Operator Influence on Blinded Diagnostic Accuracy of Point-of-Care Antigen Testing for Group A Streptococcal Pharyngitis - Carla Penney; Robert Porter; Mary O’Brien; Peter Daley (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Acute pharyngitis caused by Group A Streptococcus (GAS) is a common presentation to pediatric emergency departments (ED). Diagnosis with conventional throat culture requires 18–24 hours, which prevents point-of-care treatment decisions. Rapid antigen detection tests (RADT) are faster, but previous reports demonstrate significant operator influence on performance. Objective. To measure operator influence on the diagnostic accuracy of a RADT when performed by pediatric ED nurses and clinical microbiology laboratory technologists, using conventional culture as the reference standard. Methods. Children presenting to a pediatric ED with suspected acute pharyngitis were recruited. Three pharyngeal swabs were collected at once. One swab was used to perform the RADT in the ED, and two were sent to the clinical microbiology laboratory for RADT and conventional culture testing. Results. The RADT when performed by technologists compared to nurses had a 5.1% increased sensitivity (81.4% versus 76.3%) (p=0.791) (95% CI for difference between technologists and nurses = −11% to +21%) but similar specificity (97.7% versus 96.6%). Conclusion. The performance of the RADT was similar between technologists and ED nurses, although adequate power was not achieved. RADT may be employed in the ED without clinically significant loss of sensitivity.